Pengaruh Desain Produk dan Persepsi Harga Terhadap Keputusan Pembelian di Toko Global Batik - Anissa Praweswari; Vina Meliana (Research and Community Service UNIVERSITAS KALBIS, 2025)
This study aims to analyze the influence of product design and price perception on purchase decisions at Toko Global Batik. A quantitative approach was employed, using purposive sampling techniques involving 100 respondents. Data were collected through questionnaires and analyzed using simple and multiple linear regression methods. The findings indicate that product design has a significant influence on purchase decisions. An attractive and trend-appropriate design can enhance consumer interest and add value to batik products. Furthermore, price perception also has a significant positive effect on purchase decisions. Consumers tend to choose products that are perceived to offer a balance between price and quality, making competitive pricing strategies a crucial factor in attracting customers. Simultaneously, product design and price perception contribute significantly to purchase decisions, highlighting their critical role in enhancing product appeal and customer satisfaction. The practical implications of this study for business practitioners emphasize the importance of continuous innovation in product design that aligns with market preferences and the implementation of competitive pricing strategies that suit consumers' purchasing power. These efforts are essential to expanding market reach and maintaining customer loyalty.